Situation Report: Bulgaria, 15 October 1964 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. New Bulgarian Ambassador to Sweden Shortage of Foreign Currency Cuban Government Trade Delegation in Sofia Bulgarian Health Delegation to U.A.R.